Computer technology and networking for the neurodiagnostic and sleep laboratory. - Kessler D (American Journal of Electroneurodiagnostic Technology, 2004)
The purpose of this article is to help those in neurodiagnostics and in sleep diagnostics have a better understanding of the technology that is available when purchasing new equipment for the laboratory. With the rapid advancements within the computer industry, neurodiagnostic and sleep equipment companies are using those newer technologies in the development of diagnostic systems. Having a good understanding of the technology utilized certainly helps those making equipment purchases be better versed during the process. With constraints on capital equipment purchases, it is important to maximize the budget so the laboratory can be equipped with the best instrumentation available.